A preliminary study of comprehensive behavioral intervention for tics in Chinese children with chronic tic disorder or Tourette syndrome - Xu, Wen; Ding, Qiang; Zhao, Ying; Jiang, Wenqing; Han, Jingjing; Sun, Jinhua (Frontiers in Psychiatry, 2022)
Objective: To investigate the adaptability of Comprehensive Behavioral Intervention for Tics(CBIT) for a Chinese population, and evaluate the efficacy of combined CBIT and pharmacotherapy (CBIT+PT) compared to CBIT or pharmacotherapy (PT) alone for reducing tics and for improving quality of life (QoL) in a sample of Chinese children with chronic tic disorders (CTD) and Tourette syndrome (TS). Method: In this 10 week randomized controlled pilot trial, 37 outpatients aged between 6-16 years affected by TS and CTD were randomly assigned to receive CBIT (n = 22) or PT (n = 15). Considering the feasibility, the patients allocated to CBIT treatment group, could further choose whether to simultaneously take medicine voluntarily, resulting in CBIT group (n=12) and a CBIT+PT group (n=10). Results: At baseline, no demographic and clinical characteristics significant differences were found between three groups(p>0.05). All three groups showed a significant reduction in tic severity after treatment assessed by Yale Global Tic Severity Scale(YGTSS) severity score(F(2,33) = 35.05, p<0.001, ηp² =0.51), CGI-I score(F(1,34) = 13.87, p=0.001, ηp² =0.29) and YGTSS impairment score(F(2,33) = 31.71, p<0.001, ηp² =0.48). The significant interactions were found between time-point and group in emotional functioning (F(2,29) = 4.39, p=0.02, ηp²=0.23), psychosocial functioning (F(2,29) = 5.93, p=0.007, ηp²=0.29) and total Qol score (F(1,34) = 3.72, p=0.04, ηp² =0.20) of Pediatric Quality of Life Inventory (PedsQL 4.0) for children suggesting a significantly larger improvement in emotional functioning, psychosocial functioning and total Qol score of the life quality in the CBIT group for children self-report, the PedsQL for proxy report only showed significant main effect of time-point in physical functioning(F(1,33) = 8.35, p=0.01, ηp²=0.2), emotional functioning (F(1,33) = 10.75, p=0.002,ηp²=0.25),,psychosocial functioning (F(1,34) = 11.38, p=0.002, ηp² =0.26) and total Qol score(F(1,34) = 13.21, p=0.001, ηp² =0.29). Conclusions: CBIT is probably effective in reducing tic severity in Chinese children with tic disorders. CBIT+PT may not be superior to CBIT alone in reducing tic severity and improving quality of life. CBIT alone showed advantageous in improving quality of life than CBIT+PT and PT alone. CBIT might be an appropriate treatment option for the patients with tic disorder in mainland China.